Faktor Penentu Struktur Modal : Bukti Empiris pada Indeks IDX30 di Bursa Efek Indonesia - Nur Fitriyanto; Slamet Haryono (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
This study aims to examine the influence of determinants of capital structure, such as business risk, dividend payout ratio, growth opportunities, sharia compliance, non-debt tax shield, profitability and tangibility toward corporate leverage by being moderated by the size of the company. The population of this study is companies that have listed on IDX30 index, with a purposive sampling method obtained by a sample of 15 companies. This study found that profitability and non-debt tax shiled had significant negative effect, business risk and firm size had significant positive effect and dividend payout ratios and sharia compliance had a significant negative effect, while future growth opportunities and firm tangibility did not significantly influence leverage company.